HUBUNGAN UMUR BETON DAN KEKUATAN TEKAN TERHADAP WAKTU AMAN PEMBONGKARAN BEKISTING - Nauval Pramesta Nugroho; Diaz Farros; Y Djoko Setiyarto (CRANE: Civil Engineering Research Journal, 2025)
Formwork removal is a critical stage in reinforced concrete construction as it is directly related to quality, safety, and efficiency. In practice, this process often relies solely on the concrete age in days, without verification of the actual compressive strength, which may lead to cracking, excessive deflection, or even permanent damage. This study aims to analyze the relationship between the development of concrete compressive strength and the capacity of primary structural elements—columns, beams, and slabs—in carrying construction loads, as a basis for determining the safe timing of formwork removal. The method employed consists of a literature review and conceptual analysis based on SNI 2847:2019, ACI 347.2-17, and compressive strength test data at ages 1–28 days. Axial and flexural capacities of the elements were compared with construction loads in accordance with SNI 1727:2020, along with an evaluation of service deflections. The analysis results indicate that columns can be safely stripped at 1 day, as their axial capacity significantly exceeds the applied loads, whereas slabs and long-span beams are safe to dismantle after 14 days, when concrete achieves at least 70% of f’c. These findings confirm that concrete age alone cannot serve as the sole reference; verification of actual strength is crucial to ensure that formwork removal is carried out safely and efficiently.